(untitled) (Journal of Hama University, 2020)
This clinical trial aimed to evaluate the soft ,dental and hard tissue changes after treatment using the Quick Fix Appliance on the maxillary joint with a splint attached to the mandibule. in this study ,16 patients (8 male,8 female) suffering from skeletal class ΙΙΙ were included .We applied two bands and four brackets on the upper arch, after ended from the alignment and leveling stage , the Components of Quick Fix appliance were applied on the maxillary and the splint attached was applied on the mandibular at the same time. Three lateral cephalometric radiographs were taken in three different time ;T1 Pretreatment,T2 after active treatment,T3 after 15 month of treatment beginning. Resuts of this study were showed an improvement in the relationship between the jaws, where the ANB angle increased significanty from the statistical, and the value of the Wits appraisal increased significant in the second time of treatment. This clinical trial showed that effectiveness of the Quick Fix Appliance on the maxillary Joint with a splint attached to the mandibular in causing skeletal changes, where the ANB angle improved by 1.94 degree